Interleukins and Some Physiological Parameters in Patients with Autoimmune Thyroid Disorders - Thikra Majid Muhammed; Qabas Huussein Allawi; Hala Mahdi Hamad (Academia Open, 2025)
General Background: Autoimmune thyroid diseases (ATDs), such as Graves’ disease and chronic autoimmune thyroiditis, are among the most prevalent endocrine disorders characterized by immune-mediated thyroid dysfunction. Specific Background: Cytokines and immune markers play pivotal roles in the pathogenesis of ATDs, yet their association with hematological indices and ovarian reserve markers, such as Anti-Müllerian Hormone (AMH), remains underexplored. Knowledge Gap: Despite the known role of interleukins in autoimmune conditions, limited data exist linking IL-10, IL-17, and IL-18 levels with hematological and reproductive parameters in ATD patients. Aims: This study aimed to assess immunological (IL-10, IL-17, IL-18, AMH) and hematological (Hb, WBC, PLT) parameters in ATD patients compared to healthy individuals. Results: Findings revealed significantly higher serum IL-10, IL-17, and IL-18 levels in ATD patients, while AMH and hemoglobin were markedly reduced. White blood cell and platelet counts were significantly elevated, suggesting immune-driven hematopoietic alterations. Novelty: This study provides integrated evidence linking cytokine dysregulation with hematological and ovarian reserve disturbances in ATD, highlighting potential biomarkers for disease activity. Implications: The results underscore the need for cytokine profiling in ATD management and suggest that IL-10 and IL-18 may serve as predictive indicators for immune and reproductive dysfunction in affected individuals.Highlight : The study found significant increases in IL-10, IL-17, and IL-18 levels among patients with autoimmune thyroid disorders. Patients showed lower AMH and hemoglobin levels, with higher WBC and platelet counts compared to controls. These results emphasize the role of cytokines in immune and hematological alterations associated with autoimmune thyroid disease. Keywords : Autoimmune Thyroid Dysfunction, IL-18, IL-17, AMH, IL-10